ANALISIS FINANSIAL USAHA GULA AREN DI KECAMATAN MAIWA KABUPATEN ENREKANG (Analysis financially Effort Sugar Aren in The District Maiwa District Enrekan) - -, Irmayani; -, M. Syahrul; -, Arman (Jurnal Ilmiah Ecosystem, 2020)
This research was conducted in Maiwa district, Enrekang Regency, starting from June to August two thousand and eighteen. This study aims to determine the income of palm sugar craftsmen, analyzing the amount of production of palm sugar craftsmen and knowing the feasibility of farming the sugar palm craftsmen in Maiwa District, Enrekang Regency. This type of research uses quantitative research. The data used in this study consists of primary and secondary data. Data collection techniques used are observation and interviews directly with each respondent. The subjects of this research were 37 sugar palm craftsmen in Maiwa Subdistrict, Enrekang Regency. The results of this study indicate that the income obtained by palm sugar craftsmen every one time of production is Rp. 29.000 The value of R / C Ratio obtained is Rp. 1,16 based on criteria, if the R / C Ratio is > 1, then the palm sugar business is worth developing. R / C Ratio. 1,16 means that each use of infut is Rp. 1 can produce an output of 1,16, in other words the profit obtained is 1,16 Means that palm sugar business is economically intended and feasible to develop. From the results of data processing in palm sugar processing business during the production period (1 week) in the district Maiwa Enrekang Regency shows that the value of R / C Ratio obtained by palm sugar craftsmen on average 1,16 means that the business is economically feasible to cultivate, because every investment expenditure of Rp. 1, the result obtained is Rp. 1,16.